Production of plywood with phenolic and melamine resin without formaldehyde Produção de painéis compensados com resina fenólica e melamínica sem formaldeído - Stupp A.M.* (2017)
The objective of this research was to evaluate the technical potential of two adhesiveswithout formaldehyde for the production of plywood for internal and external not sheltered environment. Therefore, the resins were compared with those traditionally used by the industry.The experimental plan consisted of 05 treatments: phenol resin without formaldehyde (T1) and with formaldehyde (T2), melamine urea with (T3) and without formaldehyde (T4), and urea formaldehyde resin (T5). Plywood laminate panels of Pinus taedawere produced with 07 veneersof 2.7mmthickness, with the adhesive composition and process parameters as recommended by the resin manufacturers.It was observed that external environment not sheltered, the urea melamine resin without formaldehyde has shown potential for use; since the phenolic resin without formaldehyde (powder) showed poor results, especially in the bonding quality. For indoors, the resin melamine urea formaldehyde-free introduced himself as a potential in terms of technological properties for replacement of urea formaldehyde.